Effect of Calorie Restriction on the Expression of Sirtuin1 as an Antiaging Biomarker - Penantian, Raya Makarim; Antarianto, Radiana Dhewayani; Hardiany, Novi Silvia (Makara Journal of Science, 2023)
Calorie restriction (CR) is the most effective method for delaying aging and preventing the onset of age-related diseases. Sirtuins constitute a family of nicotinamide adenine dinucleotide (NAD)-dependent histone deacetylases. Their activity can be regulated by NAD+/NADH levels, which are influenced by nutrient intake, a variable acted upon by CR. This review elaborates on the link between CR and sirtuin1 (SIRT1). It retrieved articles from several sources, such as ClinicalKey, PubMed, and ScienceDirect. It discusses the up-to-date knowledge of how SIRT1 acts as a nutrient sensor and regulator of molecular mechanisms. These mechanisms include the control of the cell cycle, enhancing mitochondrial quality control, activating fatty acid oxidation, and stimulating anti-inflammatory effects. Disruptions in the aforementioned mechanisms are the basis of aging. CR increases the expression of SIRT1, which enhances the biogenesis and dynamics of mitochondria, resulting in an antiaging effect. In CR, SIRT1 is activated and stimulates different pathways, especially those related to mitochondrial activity and effectiveness, leading to an antiaging effect in collaboration with other antiaging biomarkers